Characterization of cis‐regulatory elements for Fgf10 expression in the chick embryo. Issue 12 (22nd November 2018) - Kawakami, Hiroko; Johnson, Austin; Fujita, Yu; Swearer, Avery; Wada, Naoyuki; Kawakami, Yasuhiko
Abstract : Background: Fgf10 is expressed in various tissues and organs, such as the limb bud, heart, inner ear, and head mesenchyme. Previous studies identified Fgf10 enhancers for the inner ear and heart. However, Fgf10 enhancers for other tissues have not been identified.Results: By using primary culture chick embryo lateral plate mesoderm cells, we compared activities of deletion constructs of the Fgf10 promoter region, cloned into a promoter‐less luciferase reporter vector. We identified a 0.34‐kb proximal promoter that can activate luciferase expression. Then, we cloned 11 evolutionarily conserved sequences located within or outside of the Fgf10 gene into the 0.34‐kb promoter‐luciferase vector, and tested their activities in vitro using primary cultured cells. Two sequences showed the highest activities. By using the Tol2 system and electroporation into chick embryos, activities of the 0.34‐kb promoter with and without the two sequences were tested in vivo. No activities were detected in limb buds. However, the 0.34‐kb promoter exhibited activities in the dorsal midline of the brain, while Fgf10 is detected in broader region in the brain. The two noncoding sequences negatively acted on the 0.34‐kb promoter in the brain.Conclusions: The proximal 0.34‐kb promoter has activities to drive expression in restricted areas of the brain. Developmental Dynamics 247:1253–1263, 2018. © 2018 Wiley Periodicals, Inc. Key Findings: Primary culture of lateral plate mesoderm from chick embryos is used to test activities of cis‐elements of Fgf10 by luciferase reporter assays. Among 11 sequences tested, two sequences in combination with a proximal promoter showed higher luciferase reporter activities than others. The sequences with high activity in vitro did not show significant activities in developing limb buds in chick embryos. The proximal promoter showed activity in the dorsal midline of the brain in developing chick embryos